Reasons for intending to childlessness in couples aged 30-45 years: A qualitative study: childlessness in couples - Borimnejad, Leili; Bazzazian, Saeideh; Barkhordari, Fateme; Rezaiee, Nasrin (International Journal of Applied Behavioral Sciences, 2024)
Background and Aim: The fertility rate of women in Iran has fallen below the replacement level, leading to concerns about population aging. This study aimed to investigate the reasons for not intending to have children among couples aged 30 to 45 in Tehran (1401-1402). Materials and Methods: This study is a qualitative research using conventional content analysis. Purposive sampling with maximum variation was used to select participants from different backgrounds, locations, and social classes. Semi-structured interviews were conducted until saturation was reached. Data analysis was conducted using Graneheim and Lundman’s approach and MAXQDA 2022 software. Results: The results were categorized into four main themes: individual, social, political, and economic factors. Individual factors included perceptions of spousal irresponsibility, ideal standards, emotional problems, mental health problems, and addiction issues. Political factors included fear of the future and lack of security, uncertain political climate, high education costs, perception of government indifference, and political restrictions. Economic factors were the cost of children, fear of financial instability, concerns about future careers, the negative impact of children on women’s professional roles, and housing problems. Socio-cultural factors included the role of school and the importance of education. Conclusion: This study revealed the complexity of the decision-making process regarding childlessness in this age group.